Acute Medication Use in Patients With Migraine Treated With Monoclonal Antibodies Acting on the CGRP Pathway: Results From a Multicenter Study and Proposal of a New Index - Sette, Lucia; Caponnetto, Valeria; Ornello, Raffaele; Nežádal, Tomáš; Čtrnáctá, Dana; Šípková, Jitka; Matoušová, Zuzana; Sacco, Simona (Frontiers in Neurology, 2022)
Introduction. Assessing the impact of migraine preventive treatments on acute medication consumption is important in clinical evaluation. The number of acute medication intakes per each monthly migraine day (MMD) could provide insights on migraine burden and represent a new proxy of treatment effectiveness in clinical trials and real-life studies. We evaluated the effect of monoclonal antibodies acting on calcitonin gene-related peptide (CGRP) pathway on the consumption of migraine acute medication in real-life. Methods. In two headache centers in Prague (CZ), we included and followed up to 6 months consecutive patients treated with MoAbs acting on CGRP (erenumab or fremanezumab). For each month of treatment, we reported monthly drug intake (MDI) in doses of any medication, migraine-specific (MS), and non-migraine-specific (non-MS) medications, and computed a ratio between MMDs and MDI, i.e., Migraine Medication Index (MMI) for MS and non-MS medications. Results. We included 90 patients (91.1% women) with a median age of 47 (interquartile range [IQR] 42 - 51) years; 81 (90.0%) treated with erenumab and 9 (10.0%) with fremanezumab. Median MMDs decreased from 11 (IQR 8-14) at baseline to 4 (IQR 2-5) at Month 3 (p<0.001 vs baseline) and 3 (IQR 2-6) at Month 6 (p<0.001 vs baseline). Median MDI decreased from 15 drug intakes (IQR 11-20) at baseline to 4 drug intakes (IQR 2-7) at Month 3 (p<0.001) and 4 drug intakes (IQR 2-7) at Month 6 (p<0.001). The corresponding MDIs for MS medications were 10 (IQR 6-14) at baseline, 3 (IQR 1-5, p<0.001) at Month 3, and 2 (IQR 0-4, p<0.001) at Month 6. MDIs for non-MS medications were 4 (IQR 0-9) at baseline, 1 (IQR 0-3, p<0.001) at Month 3 and at Month 6. Median MMI decreased from 1.32 (IQR 1.11-1.68) at baseline to 1.00 (IQR 1.00-1.50, p<0.001) at Month 3 and 1.00 (IQR 1.00-1.34, p<0.001) at Month 6. Conclusions. We confirmed that MoAbs acting on CGRP pathway decrease acute migraine medication consumption. We proposed a new index that can be easily applied in clinical practice to quantify migraine burden and its response to acute medication. Our index could help optimizing migraine acute treatment in clinical practice.